2022
DOI: 10.56556/gssr.v1i1.311
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of research in the study of the implementation of the circular economy in the preservation of water resources

Abstract: Under the current consumption model, the depletion of natural resources, specifically water, is a reality that we will face if we do not promote a paradigm shift: resources can be reused leaving behind the traditional patterns of taking, manufacturing and discarding. Under this premise, in recent years, the concept of circular economy, an economic premise interrelated with sustainability has become an alternative for responsible consumption. The objective is to maintain water sources, if possible, through cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…To ensure ecological sustainability, policymakers should also consider the moderating effects of imposing environmental taxes (green taxes) on other key factors such as energy use behavior, energy consumption sources, and green technologies [37][38][39]. Make Taiwan's entire medical industry supply chain gradually decarbonize to achieve the best goal of sustainable development of the healthcare industry [52][53][54].…”
Section: Conclusion and Policymentioning
confidence: 99%
“…To ensure ecological sustainability, policymakers should also consider the moderating effects of imposing environmental taxes (green taxes) on other key factors such as energy use behavior, energy consumption sources, and green technologies [37][38][39]. Make Taiwan's entire medical industry supply chain gradually decarbonize to achieve the best goal of sustainable development of the healthcare industry [52][53][54].…”
Section: Conclusion and Policymentioning
confidence: 99%
“…Adebanjo and Shakiru 7 studied the relationship between air pollution and economic development and found that there was a significant relationship between air pollution variables and economic growth and that economic growth had both positive and negative effects on air pollution. Moreno Rocha and Luis 8 conducted a study on water recycling utilization. They adopted Scopus database and text mining program VantagePoint to identify 425 records and finally found that 83% of them suggested an increasing trend of water recycling economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the comparison of results, this study will also delve into the challenges and limitations associated with the application of both methodologies in the specific context of Colombia. These challenges may include obtaining accurate and reliable data, adapting to changing energy market conditions, and considering socio-economic factors in decision making [11]. This analysis seeks to provide a more complete and critical view of both methodologies, allowing decision makers in Colombia and other places with similar challenges to better understand the advantages and limitations of each approach.…”
Section: Introductionmentioning
confidence: 99%